2015
DOI: 10.1590/s1413-70542015000600009
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba Peel in the Production of Cookies for School Food: Technological and Sensory Aspects

Abstract: Jabuticaba (Myrciaria cauliflora Berg) is agreatly appreciated fruit with nutritional importance, primarily found in the majority of Brazil. Its peel is a discarded by-product of the Brazilian agroindustry. The objective of this study was to develop cookie formulations with partial replacement of wheat flour (WF) and oat flour (OF) by jabuticaba peel meal (JPF), analyzing the technological aspects of the elaborate cookies and evaluating the acceptance of the selected product. All regression models of the cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
11
0
6
Order By: Relevance
“…Some studies have shown the feasibility of substituting wheat flour with fruit skin flours (from melon, jaboticaba and banana, amongst others) in several products (cakes, cookies and bread). The results suggested good sensory acceptance and market potential (AL-SAYED; AHMED, 2013;ZAGO et al, 2015;ESHAK, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the feasibility of substituting wheat flour with fruit skin flours (from melon, jaboticaba and banana, amongst others) in several products (cakes, cookies and bread). The results suggested good sensory acceptance and market potential (AL-SAYED; AHMED, 2013;ZAGO et al, 2015;ESHAK, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al 11 observed a higher content of polyphenols in the fruit peel, being almost 25 times higher than in the pulp. Therefore, it is necessary to seek alternatives for the use of jabuticaba skin by incorporating it into food products 12,15 to use its antioxidant properties 14 .…”
Section: Use Of Jabuticaba (Plinia Cauliflora) Skin In the Processingmentioning
confidence: 99%
“…Jabuticaba skin can be subjected to different processes to be used in the processing of food products. Studies have been performed with the use of flour made of jabuticaba skin to make cookies and cereal bars 13,14 . Some authors also report the direct use of its pulp and skin to produce liquor and jellies 16,18 .…”
Section: Use Of Jabuticaba (Plinia Cauliflora) Skin In the Processingmentioning
confidence: 99%
“…This fact was also discribed by Ferreira et al (2012). On the other hand, Zago et al (2015) described a positive effect of the addition of FCJ in cookie for school food. However, the authors used vanilla essence, which interfered in the sensorial evaluation of the product.…”
Section: The Bioactive Compounds and The Antioxidant Activity Found Imentioning
confidence: 99%
“…Lima et al (2011) evaluated different anthocyanin extraction processes as well as pigment stability and antioxidant activity of skin, seed and pulp. Zago et al (2015), prepared cookies for school food using jaboticaba skin, in which they evaluated only physical and sensorial characteristics.…”
Section: Introductionmentioning
confidence: 99%